Enhancing Students’ Interest in Poetry Writing Through the Culturally Responsive Teaching Approach at Vocational High School - Ida Nuraeni; Witri Wahyuni (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This study aims to improve junior high school students’ interest in poetry writing through the integration of Culturally Responsive Teaching (CRT) and Problem-Based Learning (PBL) within a Classroom Action Research framework. Methodology: The study employed Classroom Action Research (CAR) conducted in two cycles involving planning, implementation, observation, and reflection. Data were collected using a learning interest questionnaire, observation sheets, and student interviews. Quantitative data were analyzed descriptively with percentage gain, and qualitative data were analyzed thematically. Main Findings: The average interest score increased from 59.2% in the pre-cycle to 83.0% in Cycle II, with an overall gain of +23.8%. All indicators—attention, perseverance, enjoyment, and activeness—showed improvement, with activeness having the highest gain (+25.8%). Qualitative data revealed enhanced motivation, confidence, and creativity in connecting cultural themes to poetry writing. Novelty/Originality of this study: This study introduces a culturally contextualized, problem-based approach to poetry writing that merges CRT and PBL principles. It advances existing knowledge by demonstrating how integrating cultural relevance with collaborative problem-solving strategies can significantly increase student engagement and creativity in literary education.